2017
DOI: 10.1017/cjn.2017.267
|View full text |Cite
|
Sign up to set email alerts
|

The Worried Well? Characteristics of Cognitively Normal Patients Presenting to a Rural and Remote Memory Clinic

Abstract: We observed a pattern of differences unfold between the "worried well" patients and those with cognitive disease. No one variable was pathognomonic of a "worried well" patient. However, taking all the above into account when evaluating a patient may help clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…5 As there are no definitive predictors of who will develop dementia and who will not, it is important to create a Will, Power of Attorney, and Advanced Healthcare Directive when one is still in good health. 21 Limitations to this study include a relatively small sample size and a cross-sectional study design where patient follow-up is not reported. Longitudinal follow-up would benefit future research in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 As there are no definitive predictors of who will develop dementia and who will not, it is important to create a Will, Power of Attorney, and Advanced Healthcare Directive when one is still in good health. 21 Limitations to this study include a relatively small sample size and a cross-sectional study design where patient follow-up is not reported. Longitudinal follow-up would benefit future research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…19 More information on the RRMC is available elsewhere. [18][19][20][21][22][23][24][25][26][27][28] Decision-making is an increasingly important issue for patients with dementia. As the rates of dementia rise, more patients will experience irreversible cognitive incapacity and a loss of autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…19 The RRMC is a one-stop clinic and consists of an interdisciplinary team including a neurologist, neuropsychology team, physical therapist, dietician, and nurse for the streamlined assessment and management of suspected dementia cases. 19,20 Each new patient receives a standard diagnostic examination that consists of bloodwork, a non-contrast CT scan, multiple neuropsychological tests and additional investigations as indicated. 20 Using this approach, the time to diagnosis is shortened, with the goal of a diagnosis, treatment recommendation and counselling by the end of the 1-day visit.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Each new patient receives a standard diagnostic examination that consists of bloodwork, a non-contrast CT scan, multiple neuropsychological tests and additional investigations as indicated. 20 Using this approach, the time to diagnosis is shortened, with the goal of a diagnosis, treatment recommendation and counselling by the end of the 1-day visit. Each patient with a diagnosis will have a follow-up session with the memory clinic at 6 weeks, 12 weeks and then every 6 months thereafter, and more often as required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation